Is HIV in pregnancy still a disease?. (16th November 2010) - Tirlapur, SA; Johnson, M; Zhang, W; Hazell, J; Levitt, D; Joseph, T; McGregor, K; Wright, A
Abstract : Objectives: To review management and pregnancy outcomes of women with HIV (human immunodeficiency virus) in a London teaching hospital. Method: Retrospective review of HIV positive women who delivered over a two-year period between 2008–2010. Results: 43 women who were HIV positive booked at our unit. 81% (n=35) delivered in our hospital (6% miscarried and 17% delivered at their local hospitals). At the time of abstract submission, the authors only had complete data sets for women who delivered at this hospital. The mean age was 35 years. Out of 74% of women with a documented ethnicity, 85% were born in sub-Saharan Africa. 3 of the women were first diagnosed in this pregnancy. All women were offered anomaly and third trimester growth scans and screening for sexually transmitted infections at booking. They were regularly reviewed by a multi-disciplinary team. 89 % (n=31) had an undetectable viral load at delivery. 31% (n=11) achieved a vaginal delivery. 11% (n=4) had a Caesarean section for a detectable viral load and 11% had an elective Caesarean section for maternal request with an undetectable viral load. The remainder of Caesarean sections were for obstetric reasons. All women who delivered by vaginal delivery had spontaneous rupture of membranes and their babies were bathed immediately after delivery. None of the babies tested positive for the virus. Conclusion: Our management of HIV positive women in accordance with national guidelines has successfully enabled women to labour and deliver with minimum intervention and no vertical transmission.